Work, Unemployment and the New Technology - Gill Colin (Policy Press, 1985)
An important contribution to the ongoing debate about the likely impact of the new technology. Foreword, Acknowledgements, Glossary of Abbreviations, Introduction, The Impact on the Enterprise, The Automated Office, On the Shop Floor, The Unemployment Threat, The Trade Union Response, Alternative Approaches to New Technology: Scandinavia, New Technology and the Future of Work, Notes, Index.